Improving energy efficiency in food shock freezing / cooling applications - Shapoval, Bohdan; Mykoliv, Ivan (My University, 2016)
For freezing (cooling) under impact, the use of adsorption dryers is economically and technically profitable. This allows you to save energy, increases the continuous operation of production lines, improves product quality.
Keywords: dehumidification; freezing; defrosting; desiccant; осушення; заморожування; розморожування; осушувач; осушение; замораживание; размораживание; осушитель; кафедра технологічного обладнання та комп’ютерних технологій проектування